EVALUATION OF THE EFFECTIVENESS OF FACE-TO-FACE AND ONLINE MENTORING USING ZOOM MEETING IN CHANGING DEVIANT BEHAVIOUR IN JUNIOR HIGH SCHOOL STUDENTS - Mulyo Handoko (Journal of Education Technology and Inovation, 2024)
The world of school adolescents is an interesting dynamic. Generally, they want new things that they have never tried before. Something new if it implies positive actions is certainly not a problem, but if it leads to negative actions this will cause problems. School adolescents who have problems and can solve their own problems are positive. However, on the contrary, if they have a problem and cannot solve it themselves and vent it to negative actions, this means that they need the help of others. Simply put, in the perspective of guidance and counselling, people who help solve other people's problems are called counsellors. This counsellor is expected to help adolescents with problems to find the best solution according to the lightness and severity of the problems faced by these adolescents. The efforts to prevent adolescent deviant behaviour are creating a harmonious family, not generalising between adolescents with one another, developing adolescents through education, encouraging adolescents to be active in organisations, developing adolescents through interests and talents supported by routine coaching by counseling teachers both in writing, face-to-face and online using Zoom Meeting.. It is hoped that even though juvenile delinquency can be reduced so as to produce good academic and non-academic learning achievements. And then the handling techniques for adolescent deviant behaviour are: first, individual handling which includes giving instructions or advice, counselling, and psychotherapy, second, family handling, third, group handling and fourth handling of couples